Setting limits fairly : can we learn to share medical resources? - Daniels, Norman, 1942-; Sabin, James E. (New York ; Oxford : Oxford University Press, 2002)
The central idea for this volume is that we lack consensus on principles for allocating resources and in the absence of such a consensus we must rely on a fair decision-making process for setting limits on health care.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Health care rationing; Medical economics